Implementasi Kartu Kosakata Visual Guna Peningkatan Kemampuan Membaca Siswa Kelas Dua di Sekolah Dasar Baturetno 1 dalam Pembelajaran Bahasa Indonesia - Mustika Imerita Egashanti Kirdanu (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
Abstract. This research aims to improve the reading skills of second-grade students at SDN Baturetno 1 through the use of picture word cards. The methodology applied is known as Classroom Action Research (PTK), which is carried out over two cycles. The participants in this study consisted of seven second-grade students from SDN Baturetno 1. The date of the research is November 5, 2024. Data collection methods include pre-survey, reading ability assessment, pre-test, and post-test. The research findings show that the integration of picture word cards significantly improves students' reading skills. In the first cycle, the learning completeness rate was 60.14%, which increased to 80.43% in the second cycle, which showed an increase of 20.29%. In short, the use of picture word cards has been proven to be effective in improving the reading proficiency of second-grade students at SDN Baturetno 1.